2018
DOI: 10.22468/cvia.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Flow Magnetic Resonance Imaging for Cardiovascular Imaging: from Basic Concept to Clinical Application

Abstract: Magnetic resonance imaging (MRI) plays an important role in evaluation of the cardiovascular system. Two-dimensional phase-contrast MRI has been used to assess regional blood flow parameters such as flow velocity and volume and regurgitant fraction. Recently, fourdimensional (4D) flow MRI that acquires three-dimensional (3D) velocity and encodes volume coverage has been developed and applied to various clinical settings. 4D flow MRI allows retrospective flow measurement at any cross-section and 3D flow visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
2
0
2
Order By: Relevance
“…Additionally, there is a limited literature on the assessment of 4D-flow-based pressure drop and relative pressures in rTOF patients. On the other hand, numerous studies demonstrated an elevated ventricular kinetic energy (KE), vorticity, wall shear stress (WSS), and turbulent KE in the patient cohort [47][48][49]. A study by Hirtler et al reported a significantly higher intracardiac vorticity in patients with rTOF, as well as the association of a higher right vorticity with the regurgitant flow in the MPA [50].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a limited literature on the assessment of 4D-flow-based pressure drop and relative pressures in rTOF patients. On the other hand, numerous studies demonstrated an elevated ventricular kinetic energy (KE), vorticity, wall shear stress (WSS), and turbulent KE in the patient cohort [47][48][49]. A study by Hirtler et al reported a significantly higher intracardiac vorticity in patients with rTOF, as well as the association of a higher right vorticity with the regurgitant flow in the MPA [50].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostics of the operation of mechanical valves in vivo are carried out using diagnostic complexes of Doppler echocardiography, magnetic resonance imaging, electrocardiography, ultrasound tomographic velocity measurement, phonocardiography, seismocardiography, and a number of other techniques and devices [23][24][25][26]. This equipment uses various principles and mechanisms for recording hemodynamics inside the heart and in general throughout the entire cardiovascular system.…”
Section: Methodsmentioning
confidence: 99%
“…Одной из таких новых магнитно-резонансных (МР) методик является МР-программа 4D обработки изображений-«4D Flow» для оценки кровотока. Неудивительно, что ее клиническое использование вызывает нарастающий интерес в мире [6][7][8][9][10].…”
unclassified
“…Методика позволяет ретроспективно наглядно представить 3D-геометрию кровотока с цветовым картированием скоростей, направления потока в произвольно выбранных участках сосудистого русла и рассчитывать количественные показатели потока. Сканирование осуществляется на свободном дыхании, без введения контрастных препаратов и может использоваться на различных этапах динамического наблюдения, что делает методику особенно привлекательной для обследования детей [2,5,6,8].…”
unclassified